Allogeneic Hematopoietic Stem Cell Transplantation for a BCR-FGFR1 Myeloproliferative Neoplasm Presenting as Acute Lymphoblastic Leukemia. (2nd October 2012) - Haslam, Karl; Langabeer, Stephen E.; Kelly, Johanna; Coen, Natasha; O'Connell, Niamh M.; Conneally, Eibhlin
Abstract : Hematopoietic myeloproliferative neoplasms (MPNS) with rearrangements of the receptor tyrosine kinase FGFR1 gene, located on chromosome 8p11, are uncommon and associated with diverse presentations such as atypical chronic myeloid leukemia, acute myeloid leukemia, or an acute T- or B-lymphoblastic leukemia, reflecting the hematopoietic stem cell origin of the disease. A review of MPN patients with the t(8;22) translocation that results in a chimeric BCR-FGFR1 fusion gene reveals that this disease either presents or rapidly transforms into an acute leukemia that is generally unresponsive to currently available chemotherapeutic regimens including tyrosine kinase inhibitors (TKIS). The first case of a rare BCR-FGFR1 MPN presenting in a B-acute lymphoblastic phase who underwent allogeneic hematopoietic stem cell transplantation (HSCT) with a subsequent sustained complete molecular remission is described. Allogeneic HSCT is currently the only available therapy capable of achieving long-term remission in BCR-FGFR1 MPN patients.